The red swamp crayfish, Procambarus clarkii cathepsin C, participates in the innate immune response to the viral and bacterial pathogens. Issue 100 (May 2020) - Liu, Qiu-Ning; Kausar, Saima; Gul, Isma; Zhou, Hai-Ling; Abbas, Muhammad Nadeem; Dai, Li-Shang
Abstract: The cathepsin C, a lysosomal cysteine protease, involves the modulation of immune and inflammatory responses in living organisms. However, the knowledge on cathepsin C in red swamp crayfish ( Procambarus clarkii ), a freshwater crustacean with economic values, remained unclear. In the present study, we provide identification and molecular characterization of cathepsin C from P. clarkii. (Hereafter Pc-cathepsin C ). The Pc-cathepsin C cDNA contained a 1356 bp open reading frame that encoded a protein of 451 amino acid residues. The deduced amino acid sequence comprised of cathepsin C exclusion domain and pept_C1 domain, and also catalytic residues (Cys 248, His 395 and Asn 417 ). Analysis of the transcriptional patterns of the Pc-cathepsin C gene revealed that it was broadly distributed in various tissues of P. clarkii, and it was more abundant in the hepatopancreas and gut. Following a challenge with viral and bacterial pathogen-associated molecular patterns, the expression of Pc-cathepsin C was strongly enhanced at different time points. The knockdown of Pc-cathepsin C, altered the expression of immune-responsive genes, suggesting its immunoregulatory role in P. clarkii . This study has identified and provided the immunoregulatory function of Pc-cathepsin C, which will contribute to further investigation of the molecular mechanism of cathepsin C in crustaceans. Highlights: A cathepsin C from Procambarus clarkii was identified and characterized for the first time. The expression profiles of Pc-cathepsin C in various tissues were investigated. The Pc-cathepsin C expression in the hepatopancreas, was up-regulated post LPS, PGN and Poly I:C challenge. RNA interference of Pc-cathepsin C influenced the expression of immune-related genes.